تأثير تمرينات تأهيلية لإصابة الرباط الصليبي لدى لاعبي نادي الجيش لكرة - حسن هادي الهلالي; شاكر سريح كيلان (الرياضة المعاصرة)
A search on the four-door broken down as follows 1. A search on the simple introduction about the game of football and the research problem and objectives of the research and which (to identify the effect of exercise qualifying ambition army club in the pretest and posttest) as well as the imposition of research (there are statistically significant injuries anterior cruciate ligament differences between pretest and posttest players army football club) as the research sample included (5) player out (24) for the player. 2. ensure that the door presentation of the results of statistical processing using a set of tables, and then analyzed and discussed in a scientific manner accurate and supported by scientific sources through this discussion and then to reach the goals of the research and verification of the hypothesis. 3. Conclusion included the conclusions of which (the effectiveness of the use of therapeutic exercise in the rehabilitation of injured anterior cruciate ligament in a sample search) members and recommendations, including (adoption of therapeutic exercises used by researchers for the rehabilitation of injured anterior cruciate ligament at the research sample).